Matera University City? Possible Dialogues - Presta, Ida Giulia; Mangialardi, Giovanna (Urbana, 2024)
The city is understood as a place intended for the production and dissemination of knowledge, culture and creativity, while the University, represents the place that fosters the transit of knowledge, and individuals, which forms new personalities. Matera has gone through different conditions in recent years, and in each of these, the University has been a central element in urban dynamics. The paper, therefore, investigates the evolution of the relationship between the University and Matera following the candidacy of the City as the Capital of Culture, the event (2029), and the subsequent epidemiological crisis caused by Covid-19. The purpose of the contribution is to initiate critical reflections on the dialogue between the two institutions, starting with the role that cultural inhabitants and "new" ways of living have on spatial transformations, to orient policies and/or strategies that can realign supply and demand, and that frame Matera as a university city.